Project Management for Construction Services Engineering: An Indepth Study Based On Hong Kong - Ran, Ren; Al-Odaini, Aiman (International Journal of Membrane Science and Technology, 2023)
Experts in the profession say that a Quantity Surveyor’s Day is mostly devoted to reviewing proposals from potential subcontractors. Nevertheless, a few of significant clients are still dissatisfied "A potential replacement for the current system of chosen subcontractors is domestic subcontracting, which the Hong Kong Jockey Club is looking at. Their hope is that this was make it easier for them to avoid lawsuits and conflicts with contractors. As time has progressed, the frequency with which "bills of quantities for business-related construction services" have expanded. There is little to no difference in the total cost of the offer between deals with and without BQ. Always remember to maintain a "keeping a with its help, the building services expert may create more methodical plans while keeping a careful eye on the project's finances. An old method of measuring building services projects in Hong Kong was developed by a number of the city's leading architect and quantity surveying firms in collaboration. Since the conventional method has been shown to be too complex, "assessment," QS firms are more likely to create their own system of measurement.